SANGIRAN FOR THE ARCHAEOLOGIST A SHORT GUIDE FOR STUDENTS - Berkala Arkeologi (BRIN, 1989)
To-day the most important locality of Pleistocene hominids in Southeast Asia is Sangiran. This is where Homo erectus fossils come from, to which species the famous Pithecanthropus and Meganthropus belong. Geographically or physiograplhically the area of Sangiran can be described as a basin surrounded by hills, of which the highest summits lie c1bout 180 m above sea level. From a geological point O'f view, however, Sangiran is a dome, where different deposits have been pushed upwards. As a result of subsequent erosion splendid stratigraphic sections are to be found, where Pleistocene and older deposits are exposed.